A ductile fracture criterion under warm-working conditions based on the multiscale model combining molecular dynamics with finite element methods. (February 2022) - Niu, Liqun; Zhang, Qi; Ma, Yingsong; Chen, Yujie; Han, Bin; Huang, Ke
Highlights: Micro-void-nucleation is promoted by elevated temperature. A multiscale ductile fracture criterion considering the Lode parameter, stress triaxiality, and temperature is developed by molecular dynamics and representative volume element. The average absolute error of the New criterion is smaller than the Lou criterion, the B&W criterion and the Shang criterion. The fracture loci of additive manufacturing AlSi10Mg in warm-working conditions are constructed by the New criterion. Abstract: The ductile fracture (DF) criterion has an important guiding significance for process simulation in predicting material safety and formability. However, knowledge regarding DF micro-mechanisms, especially temperature impact, is limited. Temperature impacts micro-void-nucleation via molecular dynamics simulations, and temperature impacts mesoscale-void-growth via representative volume element simulations of periodic boundary conditions are studied. Results of these simulations show that elevated temperature promotes micro-void-nucleation but has no apparent effect on mesoscale-void-growth. This paper develops an uncoupled DF criterion considering the effects of micro-void-nucleation, mesoscale-void-growth, and void-coalescence on damage from the multiscale viewpoint. The range of application of the developed criterion is from room temperature to below recrystallization temperature. The fracture locus of AA 2024-T351 alloy and 316LN stainless steel is constructed using the criterion and compared with the Lou criterion (Lou et al., 2012), the B&W criterion (Bai and Wierzbicki, 2008), and the Shang criterion (Shang et al., 2018). The results show that the New criterion provides better predictability. The DF criterion is also calibrated and validated using seven types of specimens processed from additive manufacturing AlSi10Mg. The Force-stroke curve and fracture morphology indicate that the criterion satisfactorily predicts DF onset in warm-working conditions and at various stress states. Therefore, the present study provides an in-depth understanding of the micro-mechanism of temperature on DF.